Glucuronidation of icaritin by human liver microsomes, human intestine microsomes and expressed UDP-glucuronosyltransferase enzymes: identification of UGT1A3, 1A9 and 2B7 as the main contributing enzymes - Wang, Li (Xenobiotica, 2017)
Icaritin is a natural flavonoid with anti-osteoporosis activity. This study aimed to characterize icaritin glucuronidation by pooled human liver microsomes (HLM) and pooled human intestine microsomes (HIM), and to determine the contribution of individual UDP-glucuronosyltrans-ferase (UGT) enzyme to icaritin glucuronidation. Glucuronidation rates were determined by incubating icaritin with uridine diphosphate glucuronic acid (UDPGA)-supplemented microsomes. Kinetic parameters were derived by appropriate model fitting. Relative activity factors and activity correlation analysis were performed to identify main UGT isoforms. UGT1A3, 1A7, 1A8, 1A9 and 2B7 were mainly responsible for catalyzing the formation of two glucuronides (G1 and G2). Icaritin 3-O-glucuronidation (G1) was significantly correlated with Chenodeoxycholic acid (CDCA) glucuronidation (r = 0.787, p = 0.002), propofol glucuronidation (r = 0.661, p = 0.019) and Zidovudine (AZT) glucuronidation (r = 0.805, p = 0.002). Similarly, icaritin 7-O-glucuronidation (G2) was also correlated with CDCA glucuronidation (r = 0.640, p = 0.025), propofol glucuronidation (r = 0.592, p = 0.043) and AZT glucuronidation (r = 0.661, p = 0.019). In addition, UGT1A3, 1A9 and 2B7 contributed 37.5, 33.8 and 21.3% for G1 in pooled HLM, respectively. Also, UGT1A3, 1A9 and 2B7 contributed 34.3, 20.0 and 8.6% for G2 in pooled HLM, respectively. Icaritin was subjected to significant glucuronidation, wherein UGT1A3, 1A7, 1A8, 1A9 and 2B7 were main contributing enzymes.